Vulnerability and Legal Protection of Indonesian Women Migrant Workers - Kadir Jaelani, Abdul; Anila Robbani; Doniyorbek Baxtiyor Ugli Imomniyozov; Wan Mohd Khairul Firdaus Wan Khairuldin; Abdul Hanis Embong (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
International labor migration has become an important livelihood strategy for many Indonesians in response to limited domestic employment opportunities and persistent economic pressures. Nevertheless, Indonesian women migrant workers remain highly vulnerable to human rights violations, unsafe working conditions, and social insecurity, particularly in the domestic, construction, and manufacturing sectors. This study aims to examine the effectiveness of protection programs for Indonesian women migrant workers by drawing lessons from Southeast Asian experiences, with specific attention to socio-demographic characteristics, economic drivers, and placement channels that shape migration patterns. The research employs a qualitative normative and socio-legal approach, combining regulatory analysis, policy review, and secondary data from relevant institutional reports and academic literature. The findings indicate that low educational attainment, limited employment opportunities in regions of origin, and reliance on informal placement networks significantly increase workers’ exposure to exploitation and rights abuses. Government protection programs implemented at the pre-departure, placement, and post-return stages demonstrate substantial potential to reduce these risks when executed in a consistent and coordinated manner. Pre-departure training enhances legal awareness and work readiness, consular and protection services contribute to case handling in destination countries, and reintegration programs support social and economic recovery upon return. However, the overall effectiveness of these measures remains constrained by weak supervision of recruitment agencies, uneven training quality, and limited protection access for domestic workers. The study concludes that strengthening formal placement channels, improving migration literacy, and enforcing stricter oversight are essential to achieving safe, dignified, and sustainable labor migration for Indonesian women migrant workers.